2018
DOI: 10.1111/jace.15860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZrB2 content on phase assemblage and mechanical properties of Si3N4–ZrB2 ceramics prepared at low temperature

Abstract: Based on the previous work on Si3N4–ZrB2 [Wu et al. J Eur Ceram Soc;2017,37:4217], the influence of ZrB2 addition on the phase and microstructure evolution of Si3N4–ZrB2 composites was emphatically investigated, and the mechanical properties were compared with pure Si3N4 ceramics. It was revealed that the ratio of β‐ to (α+β)‐Si3N4 significantly increased from 14.3% in pure Si3N4 ceramics to 39.8% in Si3N4 with 15 vol% ZrB2 addition, indicating that the introduction of ZrB2 promoted α‐ to β‐Si3N4 phase transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…17,18 Among many additives, zirconium-based compounds (e.g., ZrB 2 , ZrC, ZrN, and ZrO 2 ) are regarded as ideal candidates with remarkable mechanical and high-temperature stability. [19][20][21] Guo et al 22 prepared a ZrB 2 -containing Si 3 N 4 -based composite at a low temperature of 1500 • C. It was found that the addition of ZrB 2 promoted the phase transition of Si 3 N 4 from α to β, and the obtained composite exhibited improved fracture toughness and bending strength of 9.8 MPa⋅m 1/2 and 702.0 MPa, respectively. Sayyadi-Shahraki et al 23 Although promising, the methods involving processing and preparation of ceramic composites still face practical difficulties, which weaken the final properties of the ceramic composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Among many additives, zirconium-based compounds (e.g., ZrB 2 , ZrC, ZrN, and ZrO 2 ) are regarded as ideal candidates with remarkable mechanical and high-temperature stability. [19][20][21] Guo et al 22 prepared a ZrB 2 -containing Si 3 N 4 -based composite at a low temperature of 1500 • C. It was found that the addition of ZrB 2 promoted the phase transition of Si 3 N 4 from α to β, and the obtained composite exhibited improved fracture toughness and bending strength of 9.8 MPa⋅m 1/2 and 702.0 MPa, respectively. Sayyadi-Shahraki et al 23 Although promising, the methods involving processing and preparation of ceramic composites still face practical difficulties, which weaken the final properties of the ceramic composite.…”
Section: Introductionmentioning
confidence: 99%
“…Among many additives, zirconium‐based compounds (e.g., ZrB 2 , ZrC, ZrN, and ZrO 2 ) are regarded as ideal candidates with remarkable mechanical and high‐temperature stability 19–21 . Guo et al 22 . prepared a ZrB 2 ‐containing Si 3 N 4 ‐based composite at a low temperature of 1500°C.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was reported that the incorporation of transition metal borides could lower the densification temperature and enhance fracture toughness while maintaining high hardness. [25][26][27] The transition metal cations of M 4+ and B 2− in the boride (e.g., ZrB 2 , 25 TiB 2 , 26 and HfB 2 27 ) can react with Si 3 N 4 , SiO 2 , and sintering aids to form liquid phase, reducing the viscosity of the liquid phase, resulting in low-temperature sintering and promoting α-Si 3 N 4 to β-Si 3 N 4 phase transformation. 28 Among these borides, HfB 2 exhibited the significant promotion effect on the lowtemperature densification and phase transformation of Si 3 N 4 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, Si 3 N 4 –SiC w ceramics still faced challenges such as high densification temperature and low hardness. On the other hand, it was reported that the incorporation of transition metal borides could lower the densification temperature and enhance fracture toughness while maintaining high hardness 25–27 . The transition metal cations of M 4+ and B 2− in the boride (e.g., ZrB 2 , 25 TiB 2 , 26 and HfB 2 27 ) can react with Si 3 N 4 , SiO 2 , and sintering aids to form liquid phase, reducing the viscosity of the liquid phase, resulting in low‐temperature sintering and promoting α‐Si 3 N 4 to β‐Si 3 N 4 phase transformation 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride (Si 3 N 4 ) ceramic, one of the best comprehensive performance structural ceramics, have been widely used in high-temperature process industry, such as military, aerospace and civil engineering industries, due to its excellent hardness, high bending strength, good chemical stability and superior hightemperature resistance [1,2]. Traditional manufacturing methods to obtain customer-designed and complex-shaped Si 3 N 4 parts always rely on slip casting and dry-pressing molding.…”
Section: Introductionmentioning
confidence: 99%